Influence of sociodemographic, lifestyle and genetic characteristics on maternal DHA and other polyunsaturated fatty acid status in pregnancy: A systematic review. (January 2020) - Wilson, N.A.; Mantzioris, E.; Middleton, P.F.; Muhlhausler, B.S.
Highlights: Inconsistencies were observed in the findings of individual studies. Consuming more fish/PUFA was associated with higher maternal omega-3 status. Having a higher education level was related to higher maternal omega-3 status. Higher alcohol intake was associated with a lower maternal omega-3 status. Smoking in pregnancy was associated with a lower maternal omega-3 status. Abstract/Summary: Introduction: Omega-3 DHA is important for the prevention of preterm birth, however there is limited knowledge of the determinants of omega-3 status during pregnancy. The primary objective of this systematic review was to synthesise data from existing studies assessing relationships between sociodemographic, diet, lifestyle and genetic factors and maternal DHA status. Materials and methods: The Medline, Embase, Amed, and CINAHL databases were searched for studies reporting measures of maternal omega-3 status and a sociodemographic/lifestyle/genetic characteristic. Results: Twenty-two studies were included in the final analyses. Higher dietary fish consumption/PUFA intake, higher education level and an older maternal age were associated with higher maternal omega-3 status. Higher alcohol intake, smoking and FADS genotype were each associated with lower maternal omega-3 status. Discussion: Differences in findings between studies make it difficult to draw clear conclusions about the relationship between these factors and maternal omega-3 DHA status, although socioeconomic status may play a role.